2022
DOI: 10.4028/p-338168
|View full text |Cite
|
Sign up to set email alerts
|

Optical Processing Damage Reduced by Polishing Technology with Material Removal in Elastic Mode

Abstract: Surface/subsurface processing damage on optical component can severely affect its surface mechanical properties and cause its resistance to external deformation to deteriorate. At the same time, the processing damage will also affect the surface quality. The surface processing defects are the main reasons leading to the decrease in the laser induced damage threshold in high-density laser system. In this paper, the damage formation mode and morphology of the traditional optical processing methods based on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Molecular dynamics simulations were used in Ref. [20] to show that the band gap on the silica surface is significantly smaller than that of the bulk structure (Figure 4), indicating that surface atoms are more likely to have chemical reactions with external atoms than the bulk atoms. Previous studies have shown that when the IBS removal depth is g nm, ion sputtering damage will occur in the shallow layer of fused silica overall photothermal weak absorption intensity of the HF acid-etched s duced by IBS, the structure damage on the shallow surface caused by sp ates the change in material characteristics, which further improves the ph absorption intensity of the corresponding area after immersion.…”
Section: Discussion: Mechanism Of Surface Hydroxylation Of Fused Silicamentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dynamics simulations were used in Ref. [20] to show that the band gap on the silica surface is significantly smaller than that of the bulk structure (Figure 4), indicating that surface atoms are more likely to have chemical reactions with external atoms than the bulk atoms. Previous studies have shown that when the IBS removal depth is g nm, ion sputtering damage will occur in the shallow layer of fused silica overall photothermal weak absorption intensity of the HF acid-etched s duced by IBS, the structure damage on the shallow surface caused by sp ates the change in material characteristics, which further improves the ph absorption intensity of the corresponding area after immersion.…”
Section: Discussion: Mechanism Of Surface Hydroxylation Of Fused Silicamentioning
confidence: 99%
“…Molecular dynamics simulations were used in Ref. [20] to sho gap on the silica surface is significantly smaller than that of the bulk stru indicating that surface atoms are more likely to have chemical reactions oms than the bulk atoms. On the other hand, the waviness of microscopic fluctuations on the solid surface is mainly manifested in the form of lattice defects, vacancies, and dislocations at the atomic scale.…”
Section: Discussion: Mechanism Of Surface Hydroxylation Of Fused Silicamentioning
confidence: 99%
See 1 more Smart Citation